Empirically Derived Profiles of Teacher Stress, Burnout, Self-Efficacy, and Coping and Associated Student Outcomes - Herman, Keith C.; Hickmon-Rosa, Jal’et; Reinke, Wendy M. (Journal of positive behavior interventions, 2018)
Understanding how teacher stress, burnout, coping, and self-efficacy are interrelated can inform preventive and intervention efforts to support teachers. In this study, we explored these constructs to determine their relation to student outcomes, including disruptive behaviors and academic achievement. Participants in this study were 121 teachers and 1,817 students in grades kindergarten to fourth from nine elementary schools in an urban Midwestern school district. Latent profile analysis was used to determine patterns of teacher adjustment in relation to stress, coping, efficacy, and burnout. These profiles were then linked to student behavioral and academic outcomes. Four profiles of teacher adjustment were identified. Three classes were characterized by high levels of stress and were distinguished by variations in coping and burnout ranging from (a) high coping/low burnout (60%) to (b) moderate coping and burnout (30%), to (c) low coping/high burnout (3%). The fourth class was distinguished by low stress, high coping, and low burnout. Only 7% of the sample fell into this Well-Adjusted class. Teachers in the high stress, high burnout, and low coping class were associated with the poorest student outcomes. Implications for supporting teachers to maximize student outcomes are discussed.